Electron correlations in narrow energy bands: ground state energy and metal-insulator transition - Didukh, L.; Skorenkyy, Yu. (Condensed Matter Physics, 2000)
The electron correlations in narrow energy bands are examined within the framework of the Hubbard model. The single-particle Green function and energy spectrum are obtained in a paramagnetic state at half-ﬁlling by means of a new two-pole approximation. Analytical expressions for the energy gap, polar states concentration and energy of the system are found in the ground state. Metal-insulator transitions in the model at the change of bandwidth or temperature are investigated. The results obtained are used for interpretation of some experimental data in narrow-band materials. В данiй роботi електроннi кореляцiї у вузьких енергетичних зонах вивчаються в рамках моделi Габбарда. За допомогою нового двополюсного наближення знайдено одночастинкову функцiю Грiна та енергетичний спектр у парамагнiтному станi при половинному заповненнi. В основному станi знайдено аналiтичнi вирази для ширини енергетичної щiлини, концентрацiї полярних станiв та енергiї системи. Дослiджено переходи метал-дiелектрик при змiнi ширини зони та при змiнi температури. Отриманi результати використанi для iнтерпретацiї деяких експериментальних даних для вузькозонних матерiалiв.